Nosocomial Transmission of Coronavirus Disease 2019: A Retrospective Study of 66 Hospital-acquired Cases in a London Teaching Hospital. (20th June 2020) - Rickman, Hannah M; Rampling, Tommy; Shaw, Karen; Martinez-Garcia, Gema; Hail, Leila; Coen, Pietro; Shahmanesh, Maryam; Shin, Gee Yen; Nastouli, Eleni; Houlihan, Catherine F
Abstract: Coronavirus disease 2019 (COVID-19) can cause deadly healthcare-associated outbreaks. In a major London teaching hospital, 66 of 435 (15%) COVID-19 inpatient cases between 2 March and 12 April 2020 were definitely or probably hospital-acquired, through varied transmission routes. The case fatality was 36%. Nosocomial infection rates fell following comprehensive infection prevention and control measures.